Tattwa-SPR: A Culturally Responsive Digital Formative Assessment Framework for Vocational Education - Gusti Ayu Dessy Sugiharni; Putu Sabda Jayendra; Anak Agung Istri Putera Widiastiti (CV FOUNDAE, 2026)
Vocational education continues to face challenges in connecting applied mathematics with workplace competencies while systematically incorporating local cultural values into authentic assessment. Although digital assessment has advanced formative feedback practices, few studies have developed culturally responsive assessment systems that simultaneously integrate vocational competencies, mathematical reasoning, and indigenous values within a unified assessment framework. This study developed and validated Tattwa-SPR, a culturally responsive digital assessment framework that integrates applied mathematics, food and beverage (F&B) competencies, and Balinese Tattwa values through a Single-Point Rubric to support formative assessment in vocational education. Employing the Borg and Gall research and development framework, the study involved needs analysis, collaborative prototype design, expert validation, and limited classroom implementation in a vocational high school in Denpasar, Bali, Indonesia. Data were collected through interviews, focus group discussions, expert validation, classroom observations, and user practicality questionnaires. The findings demonstrate that the framework achieved high content validity and practical usability while enabling the systematic translation of abstract cultural values into observable assessment indicators. The digital platform also streamlined teacher feedback through automated reporting and encouraged students to engage independently with personalized performance dashboards, promoting greater self-regulation during learning. This study extends the literature on culturally responsive assessment by demonstrating how indigenous values, vocational competencies, and applied mathematics can be integrated within a digital formative assessment framework. The proposed model offers a transferable approach for designing authentic digital assessment systems that strengthen feedback quality, learner autonomy, and culturally responsive vocational education across diverse educational contexts.